THE COUNTER DISCOURSE OF AFRO-AMERICAN FATHER AS SEEN ON THE PURSUIT OF HAPPYNESS (2006) MOVIE - Ledy Heryanti; Elisabeth Ngestirosa Endang Woro Kasih (Linguistics and Literature Students' Journal, 2022)
Stereotyping and stereotypes have always been an element of human society. In society and the media, there has existed a stereotype of Afro-American fathers. Studies revealed that Afro-American fathers are often absent from their children's lives. The issue tends towards Afro-American father stereotypes and has a long and complicated history in the U.S. Through this autobiography movie: The Pursuit of Happyness, Chris Gardner, as the main character and an Afro-American father, breaks the negative stereotype in the U.S. society viewing Afro-fathers. The author uses a descriptive qualitative method and stereotype theory, helped by narratology film in analyzing the data. The primary data were pictures, narration, and dialogue in The Pursuit of Happyness movie. The study found six issues considered as counter-discourse on Afro-American father stereotypes. They are educated, attentive, supporting, financially responsible, and diligent figures on Afro-American father figures. The paternal bound also exists in the figure.Keywords: Afro-American father, counter discourse, film analysis, stereotypes